Association of maternal factors with stunting in 12-23 months old children in Dili, Timor Leste - Florencia Grifit Joiner, Da Costa Hornay; Chandra, Dian Novita; Lestari, Wiji (Indonesian Nutrition Association, 2024)
Stunting, characterized by low height-for-age, is a chronic malnutrition condition that primarily manifests during the first 1,000 days of life. According to the World Health Organization (WHO 2020), the maximum acceptable prevalence of stunting is 20%. Timor Leste has a significantly higher prevalence of stunting, at 47.1%. Previous research has shown that maternal characteristics from pregnancy to child-rearing phase play an important role in stunting. This study aims to identify the relationship between maternal factors and the incidence of stunting during the first two years of life